Advances in repair of non-discoid meniscus injuries in children: a narrative review - Tian, Ye; Shen, Yong-Le; Wang, Ke-Lin; Guo, Da-Wei; Hou, Ting-Ting; Ma, Tao (Frontiers in Pediatrics, 2026)
Non-Discoid meniscus injuries in children and adolescents are generally less common than in adults. However, with the increasing number of children participating in physical exercise and the intensification of exercise intensity, the frequency of meniscus injuries is gradually rising. Currently, research on the diagnosis and treatment of meniscus tears in adults is quite advanced, and some progress has also been made in the research on the repair of meniscus injuries in children. Nevertheless, there is a lack of consensus regarding the repair of meniscus injuries in this population. This study reviews relevant literature on the treatment of meniscus injuries in children in recent years, summarizing aspects such as meniscus vascular distribution, injury classification, mechanisms of injury, and repair methods, aiming to provide a reference for the repair of meniscus injuries in children. This narrative review focuses specifically on non-discoid meniscus injuries in children and adolescents; discoid meniscus lesions, which differ from non-discoid lesions in pathogenesis, morphology, therapeutic approach and outcomes, are excluded from detailed discussion.